Impact of knowledge sharing on knowledge Acquisition among Higher Education Employees - Ravikumar, Rejitha (2022)
This paper consolidates academic studies on knowledge sharing and acquisition. An effort is made to synthesize and establish the research perspectives and the link between knowledge sharing and knowledge acquisition in higher educational institutions based on a systematic review of literature retrieved from sources such as Google Scholar and the various journals listed on Scopus. Many articles were identified that studied these two processes separately. However, the number of works that investigate the relationship between knowledge sharing and knowledge acquisition is extremely limited, particularly in the context of higher education institutions (HEI). This systematic review finds papers that explain techniques of information sharing and knowledge acquisition in higher education institutions and examines the impact of knowledge sharing on knowledge acquisition. The papers chosen draw a link between knowledge sharing and knowledge acquisition and outline the criteria that facilitate knowledge sharing. Keywords: higher educational; knowledge sharing; knowledge acquisition; systematic literature review